DEVELOPMENT OF INTEGRATED WASTE MINIMIZATION MANAGEMENT FRAMEWORK IN CONSTRUCTION INDUSTRY FOR SUSTAINABLE DEVELOPMENT - UMAR, USMAN AMINU (2018)
Construction waste is considered a major contributor of solid wastes in municipal landfills and usually accounts for 10-30% of the total waste disposed of at landfill sites in many cities around the world. Many researchers have stated that 75% of wastes generated by construction industries have residual value. They can be recycled, salvaged, and reused. As the construction sector is a primary user of natural resources, the enormous amount of construction waste imposes significant stress on the limited natural resources and places a burden on sustainable development of all the cities in both developed and developing countries